Pengaruh Strategi Pembelajaran The Influence of Multicultural Education Learning Strategies on Tolerance Attitudes - Widiastini, Ni Wayan Eka; Ni Luh Putu Agetania (Jurnal Pendidikan Multikultural Indonesia, 2024)
Intolerance and bullying are still pressing problems in the education system in Indonesia, which have an impact on the creation of a harmonious and inclusive learning environment. This problem requires an innovative educational approach to foster an attitude of tolerance and understanding between students. This study aims to explore the effect of multicultural education learning strategies on improving the attitude of tolerance of elementary school students. This study used a quasi-experimental design involving two groups, namely the experimental group that received multicultural-based learning and the control group that underwent conventional learning methods. The research instrument was a tolerance attitude questionnaire that was analyzed using inferential statistics. The results showed that the group that received the multicultural learning strategy showed a significant increase in tolerance attitudes compared to the control group. These findings indicate that multicultural education can be an effective tool in creating a more inclusive and tolerant learning environment. This study contributes to the development of multicultural education in Indonesia, especially in the context of elementary education, and provides practical recommendations for teachers and schools in implementing learning strategies that support tolerance attitudes. The output of this study is expected to be published in an indexed national journal and provide a reference for the development of multicultural education policies in the future.